Сучасний стан і формування колекцій дендрарію Національного ботанічного саду ім. М.М. Гришка НАН України - Doroshenko, O.K.; Kuznetsov, S.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
The paper gives results on taxonomy investigation arboretum collections of the M.M. Gryshko National Botanical Gardens of the NAS of Ukraine. According to data obtained general quantity of taxons makes 1005 taxons that include 674 species, 22 subspecies, 34 hybrids, 274 cultivars (forms). Data of analysis of introducents geography origins, their belonging to the life forms, causes of some species elimination, introduction capasity of some dendrarium section, families and genera complexes, genera spectrum for the collections replenishment are presented.